2010
DOI: 10.1186/1471-2148-10-336
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial laggards: multilevel selection, cooperative polymorphism and division of labour in threshold public good games

Abstract: BackgroundThe origin and stability of cooperation is a hot topic in social and behavioural sciences. A complicated conundrum exists as defectors have an advantage over cooperators, whenever cooperation is costly so consequently, not cooperating pays off. In addition, the discovery that humans and some animal populations, such as lions, are polymorphic, where cooperators and defectors stably live together -- while defectors are not being punished--, is even more puzzling. Here we offer a novel explanation based… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
51
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(59 citation statements)
references
References 86 publications
(131 reference statements)
5
51
2
Order By: Relevance
“…We note the parallel between this work and our model of cooperation over care. However, in contrast to the multilevel selection approach taken by Michod (2006) and a recent game-theoretic analysis of social role specialization (Boza and Számadó 2010), we show that social role specialization can promote the evolution of cooperation without the need to invoke grouplevel competition. We therefore propose the general hypotheses that synergistic costs and skill differences between two or more cooperative traits should confer a selective advantage to specialization, which in turn stabilizes cooperation over evolutionary time.…”
Section: Discussioncontrasting
confidence: 89%
“…We note the parallel between this work and our model of cooperation over care. However, in contrast to the multilevel selection approach taken by Michod (2006) and a recent game-theoretic analysis of social role specialization (Boza and Számadó 2010), we show that social role specialization can promote the evolution of cooperation without the need to invoke grouplevel competition. We therefore propose the general hypotheses that synergistic costs and skill differences between two or more cooperative traits should confer a selective advantage to specialization, which in turn stabilizes cooperation over evolutionary time.…”
Section: Discussioncontrasting
confidence: 89%
“…In fig. 1 (a), it is clearly shown that the cooperation level ρ c monotonously increases with the enhancement factor r for each value of h [16]. Interestingly, compared with other cases, the one with h = 0.4 leads to the optimal cooperation level [see fig.…”
Section: Resultsmentioning
confidence: 94%
“…While the prisoner's dilemma game (PDG) has become a paradigm for studying the evolution of cooperation among individuals through pairwise interactions [1,3,4,5,6,7,8,9]. As a natural extension, the N-person PDG, namely, the public goods game (PGG) for collective interactions also attracts much attention [10,11,12,13,14,15,16,17,18,19,20]. In a typical PGG, each player in a group of N individuals is entitled to adopt either cooperation (C) or defection (D).…”
Section: Introductionmentioning
confidence: 99%
“…However, frequency-dependent game theoretical models have explored the evolutionary stability of mixes of cheating and cooperative strategies in groups of non-relatives (e.g. [19,20]). These models assume that freeriders do well when they are rare because they exploit the efforts of a large number of cooperators.…”
Section: Introductionmentioning
confidence: 99%